JEJARING BISNIS KELUARGA DENGAN PERUSAHAAN MULTINASIONAL (Studi Kasus Bengkel Ravito Pro) - Ravito Zakaria Pramudhani; Made Siti Sundari; Idfi Setyaningrum (CALYPTRA, 2018)
This research is a qualitative research category using primary data and. This resaerch aims to analyze the development of family business that influenced by several important factors in the family orientation. The results in this study indicate that the dimensions in family orientation greatly affect the course of business such as traditions in business that can be derived or taught to the next generation, Stability that must be maintained in the course of business to stay consistent, loyalty in terms of commitment to family business, trust between each other in running a family business that will make the business more smoothly, interdepency in terms of mutual reliance and mutual support for each other.